Troponin Levels in Patients in Acute Phase of Stroke - Edyta Dziadkowiak; Justyna Chojdak; Maciej Guziński; Katarzyna Lewczuk; Leszek Noga; Alicja Kostecka; Bogusław Paradowski (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
Background and Purpose: The purpose of this study was to assess the correlation of cTn levels in the acute phase of ischemic stroke with the extent of stroke, the degree of disability assessed on the modified Rankin Scale, and their prognostic signifi cance. Methods: Patients were divided into 3 groups: (A) ischemic strokes, (B) ischemic strokes followed by hemorrhagic transformation, and (C) hemorrhagic strokes, excluding patients with symptoms of acute coronary syndrome. Cardiac troponin levels (cTn) were determined by venipuncture using the Abbott ARCHITECT STAT hs Troponin-I assay.